CRNA GORA, KAO POLIGON ZA TREKING TURE BICIKLOM - Dragan Martinović; Dragan Branković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
The way people live needs to be in line with the nature, directed towards nature and its preservation. There are numerous ways of getting acquainted with the nature and of learning to love it. One of the most beautiful ways to achieve this is on a bicycle, during different tracking tours. It is my wish that this thesis serve those in harmony with the nature, cycling-lovers, and potential adventurers to get in touch with the beauty of Montenegro and find out about the possibilities that it offers for cycling and organising tracking tours, and at the same time to seve as an incentive for enhancing the nuber of people willing to cycle for recreation, especially in the mountanious and coastal turist regions, thereby improving the turist offer and visits